2013
DOI: 10.1187/cbe.12-08-0129
|View full text |Cite
|
Sign up to set email alerts
|

Using a Physics Experiment in a Lecture Setting to Engage Biology Students with the Concepts of Poiseuille's Law

Abstract: A physics experiment on Poiseuille's law was performed as a demonstration in a physiology course. Students who viewed the demonstration reacted positively and increased their test performance, although the control group eventually “caught up,” despite not having seen the demonstration. Students with lower math skills who viewed the demonstration benefited slightly more than did those with higher math skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…, 2002 ). One reason students might struggle to understand bulk flow in physiology may arise from the interdisciplinary nature of fluid dynamics, which is grounded in principles of physics and is represented with multiple mathematical relationships ( Wang, 2004 ; Michael, 2007 ; Breckler et al. , 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…, 2002 ). One reason students might struggle to understand bulk flow in physiology may arise from the interdisciplinary nature of fluid dynamics, which is grounded in principles of physics and is represented with multiple mathematical relationships ( Wang, 2004 ; Michael, 2007 ; Breckler et al. , 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Classroom demonstration refers to the activities designed by the instructor to promote the active participation of the learner and better conceptual understanding [ 15 , 16 ]. While some studies have shown that demonstrations can enhance student interest and explain concepts clearly [ 15 - 17 ], there is also evidence that class demonstrations can be ineffective [ 18 ]. However, in the medical curriculum, very few studies have explored the use of student-involved activities and their influence on the learning outcome [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…A few examples are electric fishes, migrating birds and fishes, echo-location used by dolphins and bats, snake's infrared and spider's polarized vision and much more [3][4][5][6][7][8][9]. In addition, the human being itself is an interesting object for physics observations [10][11][12]. The basic physiology of humans is very similar to other animals, in particular mammals of course.…”
Section: Introductionmentioning
confidence: 99%